Perancangan Paket Wisata di Desa Hambalang Kabupaten Bogor Berbasis Wisata Sport Tourism, Alam, dan Religi - Mbulu, Yustisia Pasfatima; Rossi, Fetty Nurmala; Salsabila, Aqilla Devia; Bhilhaq, Mutiara Sani (Jurnal Ilmiah Pariwisata, 2024)
This research aims to design a tourism package based on sport tourism, nature, and religion in Hambalang Village, Bogor Regency. The research method was descriptive qualitative, collecting field survey data or direct observation in Hambalang Village, Bogor Regency. As well as conducting interviews with the Head of Hambalang Village, the Head of the tourist village, Karang Taruna, the Chair of the MUI of Hambalang Village, MSME actors, the people of Hambalang Village, and the manager of the Environmentally Friendly Village. The results obtained from designing tour packages in Hambalang Village, Bogor Regency, are in the form of sport tourism, nature, and religious tourism-based tour packages called "Hambalang AdventTour" for tourists who visit without staying overnight and the "Live In Hambalang" package for tourists who stay overnight. Hambalang Village. The "Hambalang AdventTour" package consists of 3 (three) types of options, which are differentiated based on the travel route, including Hambalang AdventTour 1, Hambalang AdventTour 2, and Hambalang AdventTour 3. Meanwhile, the "Live in Hambalang" package only consists of 2 types of packages for tourism, which are differentiated based on place of residence and tourist activities. Keywords: design of tour packages, tourism villages, sport tourism, nature tourism, religious tourism